Mediators of the Relation Between Community Violence and Sexual Risk Behavior Among Adults Attending a Public Sexually Transmitted Infection Clinic - Senn, Theresa E. (Arch Sex Behav, 2016)
Prior research shows that violence is associated with sexual risk behavior, but little is known about the relation between community violence (i.e., violence that is witnessed or experienced in one's neighborhood) and sexual risk behavior. To better understand contextual influences on HIV risk behavior, we asked 508 adult patients attending a publicly-funded STI clinic in the U.S. (54% male, M(age) = 27.93, 68% African American) who were participating in a larger trial to complete a survey assessing exposure to community violence, sexual risk behavior, and potential mediators of the community violence-sexual risk behavior relation (i.e., mental health, substance use, and experiencing intimate partner violence). A separate sample of participants from the same trial completed measures of sexual behavior norms, which were aggregated to create measures of census tract sexual behavior norms. Data analyses controlling for socioeconomic status revealed that higher levels of community violence were associated with more sexual partners for men and with more episodes of unprotected sex with non-steady partners for women. For both men and women, substance use and mental health mediated the community violence-sexual risk behavior relation; in addition, for men only, experiencing intimate partner violence also mediated this relation. These results confirm that, for individuals living in communities with high levels of violence, sexual risk reduction interventions need to address intimate partner violence, substance use, and mental health to be optimally effective.